Transregional Europe - Outhwaite, William (Emerald Publishing Limited, 2020)
Transregional Europe continues a line of argument developed in European Society (2008), Europe Since 1989 (2016) and Contemporary Europe (2017). It integrates work in human geography and planning with related scholarship in history and the other social sciences, covering public perceptions of European macro-regions and EU macro-regional planning. Are Europeans increasingly thinking, like North Americans, of their (sub-) continent in broad North/South and East/West categories? Are the macro-regional constructs such as the Danube or Baltic region identified or constructed by European policy-makers real, imaginary, or both? What is the relation between Europe and Eurasia and their respective political structures? Transregional Europe bridges the gap between stereotypical generalisations about southerners, the 'wild East', and so on and the constructions assembled by national and transnational policy-makers. It should be of interest to students of Europe within a wide range of disciplines and interdisciplinary programmes: not just sociology or European studies but also human geography, politics, economics, international relations and cultural studies.